PEMBUATAN PROGRAM PERANCANGAN TURBIN SAVONIUS TIPE-U UNTUK PEMBANGKIT LISTRIK TENAGA ANGIN - Novri Tanti (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2011)
The Savonius Wind Turbine is a drag type vertical axis wind turbine, and it operates by cupping and dragging the wind, causing the rotor to turn and generate electricity. The Savonius Wind Turbine usually has about two or three scoops or cups to catch the wind. The design allows the turbine to rotate relatively slowly, however, there is a high torque yielded from the rotation.On this research, the wind turbine Savonius type-U is designed using Matlab 7.0 with the design process starts from the needs of electrical power 100 watts and 12 volt electrical voltage and wind speed 8 m/s so obtained what is the magnitude and width of the radius of the wind turbineKeywords: wind, turbine, electrical power.